What Does Belief Have to Do with Truth?. (21st September 2018) - Fileva, Iskra
Abstract: I argue that the widely-held view that belief aims at the truth is false. I acknowledge that there is an important connection between truth and belief but propose a new way of interpreting that connection. On the account I put forth, evidence of truth constrains belief without furnishing an aim for belief.